2009
DOI: 10.1172/jci37398
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 11β–hydroxysteroid dehydrogenase type II selectively blocks the tumor COX-2 pathway and suppresses colon carcinogenesis in mice and humans

Abstract: Colorectal cancer (CRC) is a leading cause of cancer death, yet primary prevention remains the best approach to reducing overall morbidity and mortality. Studies have shown that COX-2-derived PGE 2 promotes CRC progression, and both nonselective COX inhibitors (NSAIDs) and selective COX-2 inhibitors (such as glucocorticoids) reduce the number and size of colonic adenomas. However, increased gastrointestinal side effects of NSAIDs and increased cardiovascular risks of selective COX-2 inhibitors limit their use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 56 publications
3
119
1
Order By: Relevance
“…siRNA-mediated depletion of Foxm1 caused a significant reduction in Vegf-a mRNA in cultured TRAMP C2 mouse prostate adenocarcinoma cells in vitro (Fig. 4C), a finding consistent with regulation of Vegf-a by Foxm1 in pancreatic tumor cells (42 (43)(44)(45) were all decreased, whereas Hif-1a, Spdef, and Foxf1 mRNA levels did not change (Fig. 5A).…”
Section: Discussionsupporting
confidence: 78%
“…siRNA-mediated depletion of Foxm1 caused a significant reduction in Vegf-a mRNA in cultured TRAMP C2 mouse prostate adenocarcinoma cells in vitro (Fig. 4C), a finding consistent with regulation of Vegf-a by Foxm1 in pancreatic tumor cells (42 (43)(44)(45) were all decreased, whereas Hif-1a, Spdef, and Foxf1 mRNA levels did not change (Fig. 5A).…”
Section: Discussionsupporting
confidence: 78%
“…Abundance of COX-2 has been linked to the growth and proliferation of cancerous and pre-cancerous cells (Cesario et al 2011, Khan et al 2011. Inhibiting the COX pathways can alter cancerous and precancerous cells by decreasing angiogenesis and cell growth (Banu et al 2007, Half, Sun and Sinicrope 2007, Ishizaki et al 2006, Sheng et al 1997, Suh et al 2009, Tuynman et al 2008, Zhang et al 2009). In addition, COX inhibition enhances apoptosis and enables the immune system to recognize and target the cells for destruction (Hida et al 2000, Ding, Tong and Adrian 2000, Hsu et al 2000, Souza et al 2000.…”
Section: Inflammationmentioning
confidence: 99%
“…The mechanism underlying increases in COX-2 expression in CRC is not completely understood. Recent studies have found that 11ßHSD2 mRNA levels are significantly higher in both human colonic small and large adenomas compared to adjacent normal colon tissues [40]. Immunohistochemical staining showed that increased 11ßHSD2 expression is primarily localized to adenoma epithelia and co-localized with increased COX-2 expression in human colonic adenomas.…”
Section: Cyclooxygenase-2 and Glucocorticoids In Tumorigenesismentioning
confidence: 93%
“…Long-term excessive ingestion of licorice has been reported to induce hypokalemia and elevation of blood pressure in a subset of people [66]. Although these side effects were not seen in animal experiments, studies did observe that the concentrations of glycyrrhizic acid increased levels of active glucocorticoid levels in the kidney [40]. Although 11βHSD2 inhibition may result in salt-dependent hypertension due to activation of mineralocorticoid receptor by glucocorticoids in kidney, development of locally acting enteric 11ßHSD2 inhibitors that are not systemically absorbed would be a potential therapeutic means to prevent tumorigenesis [67].…”
Section: Conclusion and Future Perspectivementioning
confidence: 98%
See 1 more Smart Citation